Impact of hyperbilirubinemia on rat cardiomyocyte injury - Jiajia Zhao; Hui Ye; Xiangjun Wu; Danying Wang; Yuanxiang Ke; Weijie Fang (BMC Cardiovascular Disorders)
Abstract Background To investigate bilirubin-induced injury in rat myocardial cells at varying concentrations. Methods The study utilized the rat cardiomyocyte cell line H9C2 and primary rat cardiomyocytes. Bilirubin-rich and control sera were prepared, and cells were cultured for 48 h with or without vitamin C. Cell viability was assessed using the CCK-8 assay, while superoxide dismutase (SOD), glutathione peroxidase (GPx), Na+/K+-ATPase, creatine kinase-MB (CK-MB), and cardiac troponin I (cTn-I) levels were measured using their respective assay kits. Results Bilirubin treatment markedly reduced the viability of H9C2 cells and primary rat cardiomyocytes compared to the control group. Additionally, it elevated the levels of cardiac injury markers, including cTn-I and CK-MB in the culture supernatant. Conversely, bilirubin exposure led to a decline in the release of GPx, Na+/K+-ATPase, and SOD in the medium. Vitamin C supplementation demonstrated partial attenuation of bilirubin-induced effects: including enhanced viability of primary rat cardiomyocytes, partially restored GPx, Na+/K+-ATPase, and SOD levels, and reduced concentrations of CK-MB and cTn-I in bilirubin-treated cells. Conclusions Hyperbilirubinemia induces concentration-dependent cardiotoxicity in rat models, while vitamin C supplementation partially mitigates bilirubin-induced myocardial damage. Trial registration Not applicable.